2018
DOI: 10.1016/j.ijadhadh.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A finite element study of fatigue crack propagation in single lap bonded joint with process-induced disbond

Abstract: This paper presents a method for predicting fatigue crack propagation in adhesive bonded composite joints with an initial full-width disbond using finite element analysis and numerical integration of the material's fatigue crack growth rate law. Fatigue tests were conducted on single lap joints. Crack lengths were monitored from four runout corners. In-situ crack growth measurements were performed by ink injection to identify the crack front profile during fatigue loading. The crack growth was modelled using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…In Figure 13(b), fatigue debonding growth from semi-circular disbond had already propagated to reach the free edges and formed a 5 mm strip disbond (similar to the initial disbond shape in the narrow width coupon joints). Compared with fatigue debonding in the "coupon" joints studied in [25], it can be found that apart from this initial fatigue cycles, fatigue debonding life of the coupon joint and wider joint do not show much difference. However, coupon joints would provide a very conservative fatigue life prediction (almost one-fourth of that of the wider joint) under the same fatigue crack growth rate (as both joints are bonded by the same adhesive).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In Figure 13(b), fatigue debonding growth from semi-circular disbond had already propagated to reach the free edges and formed a 5 mm strip disbond (similar to the initial disbond shape in the narrow width coupon joints). Compared with fatigue debonding in the "coupon" joints studied in [25], it can be found that apart from this initial fatigue cycles, fatigue debonding life of the coupon joint and wider joint do not show much difference. However, coupon joints would provide a very conservative fatigue life prediction (almost one-fourth of that of the wider joint) under the same fatigue crack growth rate (as both joints are bonded by the same adhesive).…”
Section: Discussionmentioning
confidence: 87%
“…Discussion on the importance of using an appropriate governing parameter was made in a previous study by the author [25]. In this current study, a normalised parameter, g max , is used as defined in Eq.…”
Section: Fractographymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, unknown variables in the solution domain are expressed by approximate functions. Many researchers have employed FEM to solve fracture problems [10], including fatigue crack growth [11][12][13] in engineering structures. Chen et al studied the impact of incision angle and depth on the strength [14] and crack propagation [15] of zirconia ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…The model is two‐dimensional, and it is assumed that crack growth is confined to a straight bond line. In a recent work, Liu et al presented a method for predicting fatigue crack propagation in adhesive bonded composite joints with an initial full‐width disbond using finite element analysis and numerical integration of the material's fatigue crack growth rate law. The crack growth was modelled using a fracture mechanics criterion considering two different crack propagation patterns.…”
Section: Introductionmentioning
confidence: 99%